The Difference Between Hemostasis Profiles in Type 2 Diabetes Mellitus Patients with Normal ABI Score and Abnormal ABI Score Based on Thromboelastography Examination - Gersom, Camoya; Arsana, Putu Moda; Firani, Novi Khila (Universitas Brawijaya, 2026)
BACKGROUND: Type 2 Diabetes Mellitus (DM) is a growing global problem, increasing by 8.5% within 15 years in Indonesia. Peripheral Arterial Disease (PAD) is an atherothrombotic complication associated with hemostasis disorders in diabetes, which can be identified using the Ankle Brachial Index (ABI). Thromboelastography (TEG), which quantifies dynamic changes in hemostasis, may play a role in diagnosing hemostasis disorders in Type 2 DM. OBJECTIVE: To determine the differences in hemostasis processes (primary, secondary, tertiary) based on TEG in patients with Type 2 DM. METHOD: This study was a survey conducted at the Endocrine Clinic of Saiful Anwar General Hospital from November 2020 to January 2021. The results were analyzed using case-control, difference, and correlation tests. RESULTS: Of 54 patients, 35 had normal ABI scores, and 19 had abnormal ABI scores. In TEF examination, the majority of patients were found to be normocoagulable across all levels of hemostasis profiles. The odds ratio (OR) was highest in hypercoagulable primary hemostasis (6.00) and lowest in normocoagulable tertiary hemostasis (0.53). From the Chi-square difference test, primary (p: 0.208), secondary (0.920), and tertiary (0.655) hemostasis did not show significant differences between the normal and abnormal ABI groups. Kendall’s Tau correlation test did not reveal significant relationships in primary (p: 0.505), secondary (0.777), or tertiary (0.614) hemostasis to ABI scores. CONCLUSION: There are no significant differences or correlations between hemostasis profiles in patients with Type 2 DM with normal and abnormal ABI scores.